Half- and Mixed-Sandwich Uranium Permethylpentalene Compounds - Chadwick, F; O'Hare, D (American Chemical Society, 2014)
The synthesis and characterization of a series of U(IV) permethylpentalene complexes has been enabled by the development of an effective synthesis of the new Pn*U synthon [Pn*U(μ-Cl)4][Li(TMEDA)]2, which has allowed access to a set of half-sandwich Pn*U complexes. The compounds have been characterized via variable-temperature NMR and in some cases by structural analysis. The temperature dependence of the NMR solution spectra show a complex interplay between fluxional ligand dynamics and the effects of a paramagnetic f2 uranium center. © 2014 American Chemical Society.